The Effect of Cuminum Cyminum L on Hemoglobin Levels in Tried Animals: Systematic Literature Review - Stevani Basuki Putri; Suharyo Hadisaputro; Sudirman Sudirman (STRADA : Jurnal Ilmiah Kesehatan, 2021)
The prevalence of anemia in women childbearing age in Indonesia according to Riskesdas in 2013 has increased in each age group. Anemia ini berdampak pada produktivitas dan kesehatan. Research on cumin has been carried out in several experimental animals that can be used to increase hemoglobin levels.To prove that giving cumin has an effect on hemoglobin levels in experimental animals.Systematic literature review by searching 2015-2020 articles on the Science Direct and Google Scholar databases using the PRISMA method.The content of cumin per 100 grams includes iron 66.36 mg, vitamin C 1270 IU, folic acid 10 µg, and protein 44.24 mg. The content of iron as an ingredient in the formation of hemoglobin, vitamin C, folic acid and protein plays a role in supporting the absorption and formation of hemoglobin. Cumin can increase hemoglobin level.